Microwave Heat Treatment Effects on the Microbial Profile of Some Ready-To-Eat Street Vended Snacks - P.O., Oleghe; R.D.A., Orhewere; V.A., Orhewere; J.E., Oboh (International Journal of Scientific Research in Biological Sciences, 2022)
The effect of heat treatments on the microbial population of plantain chips and roasted groundnut using microwave sterilization was carried out with the aim of improving food safety of various ready-to-eat street vended Nigerian snack foods. The samples were purchased from different food snacks vendors within Auchi Metropolis and immediately taken to the laboratory for analysis. The samples were divided into four parts and subjected to microwave heat treatments at 72oC for 10, 20 and 30 minutes with the control not treated with any form of heat. Thereafter, each sample were analysed for their microbial density and quality using standard microbiological procedures. The results revealed a reduction in the microbial density of the samples as heat treatment time increased especially among the bacteria population, but the fungal load was not as linear. The microbial quality analysis showed that plantain chips contained some microorganisms which survived the heat treatment and could be of public health importance, although their numbers were within the recommended tolerable limits for ready- to-eat foods. It is therefore imperative to educate and sensitize food producers especially ready-to-eat street vended snack food handlers on the necessary sanitary protocols needed to assure food safety during food preparations.